Workshop Pengolahan Pembuatan TeKo (Susu Tempe Kopi) pada Acara Research Camp bersama SMA Kebon Dalem Semarang - Paulus Damar Bayu Murti; Martina Widhi Hapsari; Novia Anggraeni; Raka Bachtiar Kuspradanarto; Geraldus Tegar Mahardika (Magistrorum et Scholarium: Jurnal Pengabdian Masyarakat, 2021)
This community services activity was addressed at students of SMA Kebon Dalem, Semarang city through a workshop on the processing of making TeKo (coffee tempeh milk) at the Research Camp event. The activity was carried out in the form of training on the processing of making TeKo and being a jury in journal presentations from SMA Kebon Dalem students. Tempe is a local agricultural product from Indonesia which is now worldwide due to its high protein content. The purpose of this service activity is to introduce local products that can be processed into functional drinks. The method used during the service is online through google meet, where the material from the workshop was explained first as an introduction then a TeKo processing demo was carried out. In the service activity, representatives from SMA Kebon Dalem were also invited to taste the results of the TeKo demo. The reception from respondents was very good regarding TeKo which can be used as a functional drink for those who do not like tempe itself.